Persepsi Peserta Didik Tentang Lingkungan Sekolah Dalam Pembentukan Sikap dan Karakter di SMAN 2 Pandeglang - Nazwa Fadilatun Sulis; Dinar Sugiana Fitrayadi (Journal of Innovative and Creativity, 2026)
This study aims to describe the school's strategy in creating a conducive environment, explain students' perceptions of the school environment, and identify challenges in the formation of attitudes and character at SMAN 2 Pandeglang. Using a qualitative method with a descriptive analysis approach, this study involved field observation, documentation, and in-depth interviews with informants consisting of the principal, teachers, and students. The results of the study indicate that SMAN 2 Pandeglang has implemented various strategies for strengthening culture through routine activities such as flag ceremonies, group exercise, Clean and Fun Wednesdays (RESIK), co-curricular activities, and Taqwa Fridays as a means of instilling the values ​​of discipline, responsibility, and religiosity. Students' perceptions of the school environment show positive developments, with them gradually beginning to internalize character values ​​through these habits, although behavioral inconsistencies are still found in the field. The main challenges faced include the heterogeneity of student character, limited understanding and role of parents, suboptimal maintenance of infrastructure, and the negative influence of social media that hinders students' focus and independent thinking. In conclusion, the synergy between structured school policies and the support of the physical and social environment is crucial for the success of holistic character formation in students.